Role of plasmapheresis in thyrotoxicosis: A review (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
In clinical practice, thyroid storm and severe thyrotoxicosis continue to rank among the most common endocrine emergencies. The goal of hyperthyroidism treatment is to achieve a euthyroid state as soon as possible and to maintain euthyroid status. Treatment options include surgery, radioactive iodine, and anti-thyroid medications (ATDs). When euthyroidism needs to be achieved quickly due to thyrotoxicosis and there are significant adverse effects to ATDs, plasmapheresis is a quick, dependable, and effective therapy option. Published literatures were reviewed for the role of plasmapheresis in thyrotoxicosis patients to provide immediate reduction of thyroid hormone due to severe hyperthyroidism, adverse effects of ATDs, and ineffectiveness of ATDs or non-thyroid surgery. The published literatures showed that around 80-85% of the cases were given diagnoses of Graves’ disease. The average number of therapeutic plasma exchange (TPE) sessions was 4-6, although maximum reduction of hormone was achieved in the first session rather than in subsequent sessions. TPE was associated with a 50 to 60 percent reduction in thyroid hormone levels. After plasmapheresis, total thyroidectomy, radioactive iodine (RAI), and other medical therapy were given. Based on the literature review, we conclude that plasmapheresis therapy is a quick, dependable, and efficient treatment option for patients unable to use ATDs due to their side effects and those whose hyperthyroidism does not improve with these medications. Plasmapheresis is also effective for those who need to achieve rapid reduction of thyroid hormone prior to total thyroidectomy, RAI, or non-thyroid emergency surgery. The expense of plasmapheresis and the requirement for highly specialized resources are its limitations.J Assoc Clin Endocrinol Diabetol Bangladesh, January 2022; 1 (1): 24-26